Reference-free cell type deconvolution of multi-cellular pixel-resolution spatially resolved transcriptomics data - Brendan F. Miller; Feiyang Huang; Lyla Atta; Arpan Sahoo; Jean Fan (Nature Communications, 2022)
Identifying cell-type-specific spatial patterns in ST data is critical for understanding tissue organization but current methods rely on external references. Here the authors develop a reference-free method to effectively recover cell-type transcriptional profiles and proportions.